The Role of Employee Engagement in Mediating the Effect of SHRM, Leadership Effectiveness, and Training and Development on HR Performance Management - Ahmad Zaelani Adnan; Ipa Hafsiah Yakin Ipa; P. Paroli (Golden Ratio of Human Resource Management, 2026)
This study aims to analyze the factors influencing human resource performance management in private manufacturing companies in Garut Regency. The study focuses on the effect of Strategic Human Resource Management, Leadership Effectiveness, and Training and Development on HR Performance Management, with Employee Engagement as a mediating variable. This research employed a quantitative approach using a survey method by distributing questionnaires to employees of private manufacturing companies. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that Strategic Human Resource Management and Leadership Effectiveness have a positive effect on Employee Engagement, while Training and Development has a negative effect on Employee Engagement. Furthermore, Employee Engagement has a positive effect on HR Performance Management and is proven to mediate the relationship between Strategic Human Resource Management, Leadership Effectiveness, and Training and Development on HR Performance Management. These findings indicate that employee engagement is an important factor in improving the effectiveness of human resource performance management. This study implies that companies need to strengthen their human resource management strategies and leadership effectiveness, while also reevaluating training and development programs to ensure that they are more relevant to employee needs and job demands. Therefore, effective human resource performance management can be achieved through the continuous improvement of employee engagement. These findings are consistent with previous research showing that Employee Engagement is an important variable in explaining HR Performance Management.